Republic of Poland : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
This Report on the Observance of Standards and Codes (ROSC) Data Module provides a review of Poland's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS), complemented by an in-depth assessment of the quality of Poland's national accounts, consumer price index (CPI), producer price index (PPI), government finance, monetary, and balance-of-payments statistics. It also provides a detailed assessment using the data quality assessment framework (DQAF).